South Africa and its COVID-19 prohibition predilection (Nepal Journal of Epidemiology, 2020)
The year 2020, will forever be marked by the Global pandemic, COVID-19. According to The Department of Health in South Africa until September 15, 2020 3,940,217 tests have been conducted. 651,521 positive cases have been identified, 583,126 recoveries have been reported and there has been a total of 15641 deaths. The South African government have introduced a range of parameters and laws in order to curb the spread of the virus whilst simultaneously endorsing programs to spearhead the preparedness of the healthcare system for the various waves of COVID-19 cases that have been forecast.  In conjunction with the new laws and regulations, the South African Government has exercised lockdown and restriction of movement policies. South Africa’s unique, multifaceted and strategic method of combatting the coronavirus has proven to be effective in using existing resources and redirecting both manpower and personnel, thus being of great benefit to all stakeholders and citizens within the country. The prohibition of alcohol is a unique method employed by the government, the full extent to which this policy reform has benefitted the country, its government and its citizens is yet to be fully calculated and projected as South Africa’s Coronavirus cases are still increasing on a daily basis. This policy reform will likely find itself becoming a popular trend with crisis management protocols of other countries if the long-term benefits thereof are proven to be true.